Islamic Insurance Determination Towards Economic Growth in Indonesia: An ARDL Analysis - Setia Murningsih; Arowadi Lubis; Lailatur Nur Afifah; Zanuba Qothrun Nad; Novita Dwi Pangesti (CV. Ulil Albab Corp, 2026)
This research aims to investigate the influence of Islamic insurance growth as one of the halal financial institutions towards economic growth. Total asset and gross premium are used as a proxy of Islamic insurance growth and GDP was used as a proxy of economic growth. Control variables, namely investment, unemployment, and interest rate are also included as predictor variables. We used purposive sampling methods to collect data and used quarterly secondary data for analysis and took the data from OJK, BPS, and BI for the 2014-2019 periods. The Autoregressive Distributed Lag Model is used for estimating the long and short-run relationship between independent and dependent variables. We found that all of the independent variables significantly affect the dependent variable in the long run except for the proxy of assets. Premium and Unemployment negatively affect economic growth, meanwhile, investment and interest rates have a positive effect on economic growth. Otherwise, we didn't find a significant short relationship with alpha 5% except for the lag of GDP. Keywords: GDP, Sharia Insurance, Investment, Unemployment, Interest Rates